Effect of different agents on preload force of dental implants with bio high-performance poly-ether-ether-ketone abutments - Sabina Mary Paul; Kuttae Viswanathan Anitha; Muthukumar Balasubramaniam (Elsevier, 2024)
Purpose: This study evaluated the influence of different agents such as blood, artificial saliva, and normal saline on preload force of dental implants with bio-high-performance poly-ether-ether-ketone (Bio-HPP) abutments to determine its effect on screw loosening. Methods: Forty (N = 40) Grade 5 titanium dental implant analog (GM Implant Analog; Neodent, Straumann) with Bio-HPP poly ether-ether ketone (PEEK) abutment and titanium screw was used in the study. The samples were embedded in acrylic split mold. In the control Group C, no agent was added. In the other three groups, blood (B), normal saline (N) and saliva (S) was added in the access cavity of the samples. A sequential torque of 15 Ncm, 20 Ncm, 25 Ncm, 30 Ncm up to 35 Ncm was applied with a digital torque meter (Eclatorq, model: SD-05bn, range:2.5-50 Ncm, torque accuracy: ± 2%cw). Samples were subjected to thermomechanical cyclic loading at 5-550 Celsius for 1000 cycles (Chewing simulator, CS 4.4) to simulate six months of clinical service. Preload was measured as reverse torque value (RTV). Raw data in the form of mean ± standard deviation was documented and subjected to statistical analysis. A one-way ANOVA was performed to contrast the groups. Tukey HSD test was used to determine the multiple comparison assessment (P < 0. 05). Results: A mean reverse torque value of 35 Ncm ±0.00 was observed in both control and in groups exposed to normal saline (P >.05). Measurements of 33.4 Ncm ±2.51 and 34.8 Ncm ±0.40 were found when exposed to blood and artificial saliva in order (P < .05). When compared with control, exposure to blood showed significant variation in preload (P = .03). Conclusion: A significant reduction in reverse torque force was observed when titanium implants and Bio-HPP abutments were exposed to blood, suggesting a potential risk of screw loosening (P < .05). In contrast, minimal decrease and no significant change in preload were noted with exposure to saliva and normal saline (P > .05).